Linkages in Price Level and Inflation Rate Between Cfa Franc Zone Countries and France - Nuven, Diep (IMF Working Papers; Working Paper ;, 1994)
The price level behaviors of the CFA franc zone countries with respect to the price level of France, defined in terms of long-run convergence in price level and short-run linear dependence of their inflation rates are not homogenous and have a break-point in the mid 1980s except for Congo. This paper quantifies the evolution of the price level behavior of each CFA franc zone country from 1979 to 1993 using the cointegration and error-correction model techniques. The interzone linkages are also examined using the simple vector autoregression model.